Sistem Among dalam Membentuk Karakter pada Siswa - Siti Alisia Amanda Puspita Sari; Bustanul Arifin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This article seeks to determine the application of the among systems in shaping the character of students in SMK Tamansiswa Kediri. Starting from how the planning of the among system, the implementation of the among system, and the evaluation of the among the system. The among systems that have been implemented since the Tamansiswa was first established and can still survive until now and have always been an important principle in learning at Tamansiswa. This research is research using a descriptive qualitative approach. The discussion is dynamic or open to modifying and developing according to needs and circumstances in the field. Researchers looking for data by conducting interviews with several subjects who understand the data that researchers are looking for and by observation in the Tamansiswa Vocational School in the city of Kediri. The results of the study, namely: (1) planning are carried out by determining educational goals, developing a curriculum in accordance with Tamansiswa identity and including the character in the lesson plan. (2) the implementation of the among systems is focused on the education method and the trilogy of leadership. (3) the evaluation of the among systems is done through the method of direct supervision from the School Principal.